Estimation of Blood Loss in Total Knee Arthroplasty with or Without Tourniquet - Mansoor Ali Khan; Muhammad Amin Chinoy; Rida Mohammad Gareeb; Syed Kamran Ahmed (Pakistan Journal of Medical Research, 2020)
Background: Total knee arthroplasty (TKA) is a procedure performed for end stage knee osteoarthritis to reinstate leg function, pain control and improve quality of life. The surgery, however, is associated with a substantial risk of concealed blood loss for which tourniquets have been used to control bleeding. There has been a lot of debate over the relevance and benefits of using tourniquets during TKA. It has no effect on postoperative blood loss and has been claimed to be associated with post-operative pain, nerve damage, superficial wounds infections and deep vein thrombosis. Objective: The objective of the study was to compare the degree of blood loss and its clinical relevance in patients undergoing total knee arthroplasty with and without tourniquet. Study type settings & duration: A Randomized Controlled Trial conducted at The Indus Hospital, Karachi, Pakistan from January 2015 to September 2015. Methodology: In this randomized clinical trial, patients were recruited after local IRB approval. Sample size was calculated using OpenEpi and included all patients of age 40 to 80 years of either gender with chronic osteoarthritis, according to the Kellgren-Lawrence classification grade 4 of Osteoarthritis. The study included two groups, both consisting of 25 patients each. In group A (non-intervention, tourniquet), the tourniquet was inflated to 350 mmHg after the leg had been elevated and exsanguinated, and was deflated after closing the wound and application of compressive dressing. In group B (intervention, non-torniquet), the application of tourniquet took place but it was not inflated. Instead, electrical diathermy, and application of pressure with surgical swabs was performed intra-operatively to control bleeding. Blood loss was measured using the Mercuriali’s formula. Results: There was an average blood loss of 807 ml during TKA. Group A had a mean blood loss of 604.6 (203.9) ml while a relatively higher statistically significant mean blood loss of 1010.7 (272.7) ml was noticed in the intervention group on whom tourniquets were not used (p <0.005). Conclusion: According to our study, calculated blood loss was relatively less in Group A, hereby showing that the use of tourniquet is superior to other forms of bleeding control during the surgery. We propose that the issue on the significance of the use of tourniquet during TKA verses no tourniquet use has to be decided on the basis of volume of blood loss.